Diagnosing cancer in English community pharmacies - Bradley, Stephen H; Jones, Daniel; Wood, Su; Rafiq, Meena; Bradley, Carolyn; Hamilton, William T (BMJ (Online), 2024)
Stephen Bradley and colleagues argue that plans to involve community pharmacies in diagnosing cancer are unlikely to transform cancer detection in primary care